PENGARUH KARBURASI ARANG TERHADAP KEMAMPUKERASAN BAJA ST 42 DENGAN METODE JOMINY - Yusuf; Asep Ruchiyat; Helanianto (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2022)
Hardenability is the ability of a material to harden to a certain depth utilizing heat treatment to form martensiteupon cooling to achieve a certain hardness. The hardness of a metal, especially steel, can be modified withoutadding alloying elements and is done by heat treatment. Steel's hardenability value is strongly influenced by thecarbon content (carburizing) in the steel structure. Increasing the hardness of a material can be done by addingcarbon to the object's surface during heat treatment. The Rockwell Hardness Test method measures the surfaceof the hardness. The test results on the specimens showed that the carburizing process of each specimenincreased the hardness of the surface of the specimen. The distribution of hardenability values is close to alinear line, namely the heat treatment temperature 900℃